Economic Disability Discourse: A Critical Analysis of the Reception of Riba Hadith on Social Media - Abdul Gaffar; Muhammad Hasdin Has (Institut Agama Islam Negeri Kendari, 2023)
Over the past decade, the anti-usury movement that has been heavily promoted on social media has developed, particularly among Muslims in Indonesia. This establishes a pattern for how bank employees interpret the Qur'an and Sunnah, which influences their decision to leave the company and, in turn, indirectly affects the banking and financial stability of the Muslim community. This study examines the discourse surrounding the dissemination of hadith on Instagram via xbank social media from the standpoint of hadith reception. The data collected from the official xbank Indonesia account was evaluated using exegetical reception, and it was determined that the anti-usury and anti-hijrah banking movements were founded on literal decontextualized readings. Contextual and maqasid issues pertaining to the benefits of texts are not adequately addressed in interpretation/syarah. Without a thorough analysis of the hadith’s interpretation, the hadith of usury is used to condemn the majority of banking activities. In fact, the maqāṣid hadith of the Prophet (peace be upon him) can be used to formulate modern financial system formulations so that the two do not exclude each other.